“It's my frenemy”: A qualitative exploration of knowledge and perceptions of fentanyl use during the COVID-19 pandemic in people who use drugs at a syringe services program in Philadelphia, PA - Bass, Sarah Bauerle; Kelly, Patrick J. A.; Pandit-Kerr, Sphoorti; Pilla, Jenine; Morris, Katherine; Larsen, Erin; Wisdom, Jennifer P.; Torralva, Phillip R. (Frontiers in Public Health, 2022)
Exacerbated by the COVID-19 pandemic and the proliferation of fentanyl and fentanyl analogues, overdose deaths have surged in the United States, making it important to understand how individuals who use drugs experience and perceive the risks of fentanyl use and how it has changed during the COVID-19 pandemic. Methods: Twenty clients from a Philadelphia syringe services program completed a questionnaire and in-depth interview about their fentanyl experiences from January to March 2021. These interviews were transcribed and analyzed using thematic analysis methods. Results: Sixty percent of participants were female and racial/ethnic minority. Participants indicated they believed fentanyl use accounted for most Philadelphia opioid-related overdoses and understood that fentanyl was different from other opioids. Fentanyl use was characterized as “all-consuming” by taking over lives and inescapable. While most perceived their risk of fentanyl overdose as high, there was low interest in and reported use of harm reduction strategies such as fentanyl test strips. The COVID-19 pandemic was noted to have negative effects on fentanyl availability, use and overdose risk, as well as mental health effects that increase drug use. Conclusions: The divide between perceived risk and uptake of protective strategies could be driven by diminished self-efficacy as it relates to acting on and engaging with resources available at the syringe services program and represents a potential intervention target for harm reduction intervention uptake. But the COVID-19 pandemic has exacerbated risks due to fentanyl use, making an effective, accessible, and well-timed intervention important to address the disconnect between perceived overdose risk and use of preventive behaviors.